ANALISIS KRITIS ETIKA IMMANUEL KANT DAN RELEVANSINYA DENGAN ETIKA ISLAM - Yulanda, Atika (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This paper is related to ethical issues that are very influential in human life. Ethics functions as a means of control or signs for someone to take an action. Immanuel Kant is a philosopher whose thoughts have influenced many later philosophers. Immanuel Kant's ethical thinking is based on an ethics of obligation or deontology. This ethical obligation assesses a good action based on good will or good wishes and does not see the final result of that action. The main purpose of this ethics is good intention or good will in carrying out an action. This research is a library research using primary and secondary sources to obtain data to be analyzed. The final result of this study is that Immanuel Kant's ethics are very relevant to today's life and ethics based on good will or good intentions will bring humans to be noble people and always behave honestly.